THIOSULFATE OXIDATION: CATALYSIS OF SYNTHETIC SPHALERITE DOPED WITH TRANSITION METALS - Yong X.; Schoonen M.A.A.; Strongin D.R. (My University, 1996)
The rate of thiosulfate oxidation to tetrathionate by dissolved molecular oxygen was measured in aqueous suspensions of synthetic sphalerites doped with first row transition metals (Mn, Fe, Co, Ni, Cu). Pure sphalerite and Mn-doped sphalerite show no catalytic activity for this reaction. Catalytic activity increases from Fe to Ni, which has maximum activity, with a slight decrease moving to Cu. The catalytic activity of the doped shhalerites is proportional to the concentration of dopant. This trend in catalytic activity from pure sphalerite to Cu-doped sphalerite can be explained using the band structures of these solids.